GDE2 is essential for neuronal survival in the postnatal mammalian spinal cord. Issue 1 (December 2017) - Cave, Clinton; Park, Sungjin; Rodriguez, Marianeli; Nakamura, Mai; Hoke, Ahmet; Pletnikov, Mikhail; Sockanathan, Shanthini
Abstract Background Glycerophosphodiester phosphodiesterase 2 (GDE2) is a six-transmembrane protein that cleaves glycosylphosphatidylinositol (GPI) anchors to regulate GPI-anchored protein activity at the cell surface. In the developing spinal cord, GDE2 utilizes its enzymatic function to regulate the production of specific classes of motor neurons and interneurons; however, GDE2's roles beyond embryonic neurogenesis have yet to be defined. Method Using a panel of histological, immunohistochemical, electrophysiological, behavioral, and biochemistry techniques, we characterized the postnatalGde2 −/− mouse for evidence of degenerative neuropathology. A conditional deletion ofGde2 was used to study the temporal requirements for GDE2 in neuronal survival. Biochemical approaches identified deficits in the processing of GPI-anchored GDE2 substrates in theSOD1 G93A mouse model of familial Amyotrophic Lateral Sclerosis that shows robust motor neuron degeneration. Results Here we show that GDE2 expression continues postnatally, and adult mice lacking GDE2 exhibit a slow, progressive neuronal degeneration with pathologies similar to human neurodegenerative disease. Early phenotypes include vacuolization, microgliosis, cytoskeletal accumulation, and lipofuscin deposition followed by astrogliosis and cell death. Remaining motor neurons exhibit peripheral motor unit restructuring causing behavioral motor deficits. Genetic ablation of GDE2 after embryonic neurogenesis is complete still elicits degenerative pathology, signifying that GDE2's requirement for neuronal survival is distinct from its involvement in neuronal differentiation. Unbiased screens identify impaired processing of Glypican 4 and 6 inGde2 null animals, and Glypican release is markedly reduced inSOD1 G93A mice. Conclusions This study identifies a novel function for GDE2 in neuronal survival and implicates deregulated GPI-anchored protein activity in pathways mediating neurodegeneration. These findings provide new molecular insight for neuropathologies found in multiple disease settings, and raise the possibility of GDE2 hypofunctionality as a component of neurodegenerative disease.